SrCl2 an environment friendly alternate to CdCl2 treatment for CdTe thin films solar cell application. (13th September 2019) - Hashmi, Gohar A M; Syed, Waqar A A; Hayat, Muhammad; Shah, Wiqar H; Shah, Nazar A
Abstract: The CdCl2 treatment is a an important step for CdTe absorber based solar cell, however CdCl2 is less abundant, toxic and extremely environment unfriendly. We propose strontium chloride SrCl2 as a possible environment friendly replacement which is non-toxic, abundant and provide comparable efficiency to thin film solar cell. In this work the CdTe thin film was prepared by closed space sublimation (CSS) technique, while SrCl2 was further coated by a spin coater and finally annealed at 200 °C. The structural properties including particle size, dislocation density and strain were determined. The structural analysis reveals that the films are crystalline, cubic zinc-blende structure with preferred orientation of (111) plane. Presence of SrCl2 layer causes increase in the intensities for other orientations of (220) and (311), showing material loses in the preferred orientation of (111) making it polycrystalline. Surface morphology observed by SEM shows improved uniformity with fewer defects after SrCl2 treatment. Band gap and other optical properties were determined using spectroscopic ellipsometry. Optical band gap is found in the range 1.6 eV to 1.4 eV and observed to decrease with the increasing SrCl2 content. The electrical conductivity is observed increasing with the addition of second layer. We report that the SrCl2 coated thin films are efficient, comparable and environmental friendly replacement for the CdCl2 coated CdTe thin films.